Scope of Questionnaires in the Pirls 2021 Study: Ruang Lingkup Kuesioner Dalam Studi Pirls 2021 - Aziza Amonova (Academia Open, 2022)
This scientific article explores the relationship between the living environment and various factors with student learning based on the findings of the Progress in International Reading Literacy Study (PIRLS) conducted in 2021. The study aims to investigate the influence of the living environment and other relevant aspects on students' academic achievements. The research employed a comprehensive questionnaire survey as the primary method to collect data from a diverse sample of students across different countries. The results demonstrate a significant correlation between the living environment and students' learning outcomes, highlighting the crucial role played by factors such as household socio-economic status, parental involvement, access to educational resources, and school environment. The implications of these findings underscore the importance of creating conducive living conditions and providing adequate support systems for students to maximize their learning potential. This research provides valuable insights for policymakers, educators, and stakeholders to design evidence-based interventions and policies aimed at enhancing student learning outcomes on a global scale. Highlights: The study examines the impact of the living environment and various factors on student learning based on PIRLS 2021 data. Results highlight a significant correlation between the living environment and students' academic achievements, emphasizing the role of socio-economic status, parental involvement, access to educational resources, and school environment. Findings have implications for policymakers, educators, and stakeholders in designing interventions and policies to enhance student learning outcomes globally. Keywords: Living environment, Student learning, PIRLS 2021, Factors, Academic achievements